2021
DOI: 10.21608/bmfj.2021.140350
|View full text |Cite
|
Sign up to set email alerts
|

Role of HER2 and Claudins in Subtypes of Urothelial Carcinoma Identified Bygata3 and Cytokeratin5\6 Immunohistochemical Study

Abstract: Background: Bladder cancer is globally the ninth, most common malignancy, and the thirteenth most common cause, of cancer death, associated with high morbidity and mortality, if not treated optimally. Bladder cancers can be divided into molecular subtypes, referred to luminal and basal with distinct clinical behaviors. HER2 is one of the established therapeutic targets in many cancers. Claudins are tight junction proteins, known to modulate therapy resistance in cancer cells. Aim: This study aimed to assess Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 4 publications
5
6
1
Order By: Relevance
“…In the current study, we detected high Claudin-1 expression in forty-two cases (67.7%), and low expression was noticed in the remaining twenty cases (32.3%). That is near to the percentages in the study done by Saad et al [ 19 ] whichreported high Claudin-1 expression in 60% and low Claudin-1 expression in 40% of their studied cases. Moreover, Abd El-Fattah et al [ 14 ] reported high Claudin-1 expression in 50% of carcinoma cases included in their study.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In the current study, we detected high Claudin-1 expression in forty-two cases (67.7%), and low expression was noticed in the remaining twenty cases (32.3%). That is near to the percentages in the study done by Saad et al [ 19 ] whichreported high Claudin-1 expression in 60% and low Claudin-1 expression in 40% of their studied cases. Moreover, Abd El-Fattah et al [ 14 ] reported high Claudin-1 expression in 50% of carcinoma cases included in their study.…”
Section: Discussionsupporting
confidence: 78%
“…As regards Claudin-4 expression, fifty-one cases (82.3%) demonstrated high Claudin-4 expression, and eleven cases (17.7%) demonstrated low Claudin-4 expression. In contrary Saad et al [ 19 ] and Abd El-Fattah et al [ 14 ] reported high Claudin-4 expression in 44% and 46.7% and low Claudin-4 in 56% and 53.3% of carcinoma cases included in their studies respectively. The difference observed in these results may be attributed to the difference in the number of studied cases conducted in their studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations